Risk factors for leptospira infection in female prison in Mato Grosso - Santos, Ana Katariny Ribeiro dos; Trettel, Ana Cláudia Pereira Terças; Graça, Bianca Carvalho da; Vivi, Viviane Karolina; Souza, Karine Motta de Oliveira Lima de; Lemos, Elba Regina Sampaio de; Avelar, Kátia Eliane Santos (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Incarcerated women are exposed to a potential environment precursor of risk for various types of illnesses, including leptospirosis. Aim: To identify the risk factors for Leptospira infection in female prison in the state of Mato Grosso (MT). Outlining: This is a quantitative open cohort study conducted between the years 2016, 2017 and 2018 in the Female Public Prison of a municipality in the middle-north region of MT. Results: Although there was no detection of seroreactivity among the incarcerated women, the profile points to young women, with a mean age of 31.45 years, brown, single, with education that did not exceed elementary school, with children and low income. Rodent contact was evidenced prior to incarceration, as well as in the prison environment by viewing the animal or its excreta, which may suggest the close and daily relationship between these women and rodents. Implications: The presence of the previous risk and during imprisonment reinforce the vulnerabilities to which these women are exposed from social interaction to the context of imprisonment, being fundamental propositions of health promotion and prevention of zoonoses in prisons.